Hepatotoxicity of the anionic surfactant linear alkylbenzene sulphonate (LAS) in bullfrog tadpoles - Franco-Belussi, Lilian [UNESP]; Jones-Costa, Monica; Salla, Raquel Fernanda; Souza, Bruno Fernando Santos; Pinto-Vidal, Felipe Augusto; Oliveira, Cristiane Ronchi; Silva-Zacarin, Elaine Cristina Mathias; Abdalla, Fabio Camargo; Duarte, Iolanda Cristina Silveira; De Oliveira, Classius [UNESP] (Elsevier, 2021)
The liver of anurans play an important role in metabolism, including detoxification, the biotransformation of molecules, and the storage of metabolites. Surfactants are part of domestic and industrial effluents. The effects of linear alkylbenzene sulfonate (LAS) on anuran liver remain unknown, however, some studies have evaluated the effects of LAS on the skin, gills, heart, testes, and liver of fishes. Here, we tested the hypothesis that LAS is hepatotoxic, promoting morphometric alterations in hepatocytes along with inflammation in the tissue, altering hepatic catabolism. We evaluated the effects of a LAS concentration that is considered environmentally safe in Brazilian inland waters on the liver of Lithobates catesbeianus tadpoles, including studies on morphology, morphometry, immunology, and metabolism. LAS exposure promoted enlargement of liver sinusoids and vacuolization of hepatocytes. Exposure to LAS also increased the area of mast cells and melanomacrophages (MMs). Additionally, LAS exposure increased hemosiderin inside MMs, suggesting alterations in the catabolism and storage of iron. Hepatocyte size increased after exposure to LAS, suggesting cytotoxic effects. Integrative analyses (i.e., morphometric, metabolic, and immunological) demonstrated hepatotoxic effects of LAS. These types of studies are key to understanding the negative effects of these substances on tadpole health, as these liver alterations impair anuran homeostasis.
Keywords: Hemosiderin; Hepatic melanomacrophages; Hepatocytes; Immune cells; Morphometry; Sodium dodecylbenzene sulfonate; Surfactants